Neurocriminology and evidentiary standards in Indonesian courts - Zul Khaidir Kadir; Nur Fadhilah Mappaselleng (Priviet Social Sciences Journal, 2026)
According to the Indonesian Code of Criminal Procedure, the evidentiary system in criminal law remains grounded in the principle of individual responsibility, which presumes free will. However, the incorporation of neurocriminological approaches into legal practice introduces ontological and epistemological conflicts that have not been systematically addressed by existing legal frameworks. This study aims to examine the tension between the concept of individual criminal liability and the deterministic framework of neuroscience and evaluate the admissibility of neuroscientific evidence within the criminal evidentiary system. This study employs a normative legal method with a conceptual approach. The findings indicate that Indonesia's criminal law lacks a conceptual framework capable of bridging the gap between moral culpability and biological vulnerability, thereby risking a loss of coherence in the attribution of legal responsibility to offenders. Furthermore, the absence of normative and procedural mechanisms for assessing the validity, limits, and relevance of neuroscientific evidence creates epistemic asymmetries and opens the door to bias in judicial proceedings. Under such conditions, integrating neuroscience into the legal system risks generating ambiguity in determining liability and undermining the principle of substantive justice. Accordingly, a normative reconstruction of evidentiary law is required as a foundational step to ensure legal consistency in responding to scientific advances.